(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: this study aimed to assess the drug resistant pattern of Mycobacterium tuberculosis complex (MTBC) and the risk factors associated to multidrug-resistant tuberculosis cases (MDR-TB) in upper part of southern Thailand. Methods: a total of 3238 TB cases was retrieved from a database of the office of prevention and control disease region 11. Only 1008 cases were confirmed by culture growth for Mycobacterium tuberculosis and drug-susceptibility testing (DST) during a period of 4 years (January 2013 to December 2016). The risk factors, including gender, age group, residence place, and history of treatment were analysed using multivariate logistic regression to predict the MDR-TB cases. Results: among 1008 TB cases included in study, 77.4% of them were males, 31.5% lived in rural area with median age of 45.0 years (IQR = 23.0), 27.6% were retreatment for tuberculosis, 25.9%, 10.8%, 3.0%, 10.7% and 9.1 were determined to be resistant to isoniazid, rifampicin, ethambutol, streptomycin and MDR-TB, respectively. Adjusted odds ratios (95% confidence interval) of MDR-TB were 5.4 (2.68-11.03), and 4.2 (2.10, 8.45) for retreatment patients, and on treatment patients, respectively. Conclusions: drug resistance tuberculosis is considerable problem in upper part of southern Thailand. Major risk factors involved previous history of TB treatment. Thus, it emphasizes on patients who had a history of previous TB treatment.